2011
DOI: 10.1186/1471-2482-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Modified Alvarado Scoring System as a diagnostic tool for Acute Appendicitis at Bugando Medical Centre, Mwanza, Tanzania

Abstract: BackgroundDecision-making in patients with acute appendicitis poses a diagnostic challenge worldwide, despite much advancement in abdominal surgery. The Modified Alvarado Scoring System (MASS) has been reported to be a cheap and quick diagnostic tool in patients with acute appendicitis. However, differences in diagnostic accuracy have been observed if the scores were applied to various populations and clinical settings. The purpose of this study was to evaluate the diagnostic value of Modified Alvarado Scoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
68
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 13 publications
11
68
4
2
Order By: Relevance
“…Over the last two decades different protocols have been introduced and tested by different researchers which include Lidverg, Fenyo, Christian, Ohman and Alvarado scoring system to make an early diagnosis of this sometimes very elusive disease. [24][25][26][27][28][29][30][31][32][33][34] In the present study found 13 (3.11%) cases of perforated appendix. The study done by S Salati, A Rather, and S Wani in kashmir shows higher rate of perforation.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Over the last two decades different protocols have been introduced and tested by different researchers which include Lidverg, Fenyo, Christian, Ohman and Alvarado scoring system to make an early diagnosis of this sometimes very elusive disease. [24][25][26][27][28][29][30][31][32][33][34] In the present study found 13 (3.11%) cases of perforated appendix. The study done by S Salati, A Rather, and S Wani in kashmir shows higher rate of perforation.…”
mentioning
confidence: 76%
“…35 If we compare it with previous studies in other scoring systems, results of present study were much higher ( Table 9). [25][26][27][28][29][30][31][32] Histopathology is considered as a gold standard for diagnosis of acute appendicitis. In a present study (6.69%) patients were have normal on histopathological examination.…”
mentioning
confidence: 99%
“…[35] Having used a modified Alvarado score, Kanumba et al [36] found sensitivity, specificity, and diagnostic accuracy rates to be different for men and women (95.8%, 92.9%, and 91.5% versus 88.3%, 89.7% and 87.6%, respectively). In the Lintula scoring system, however, the sex of the patient is considered a separate parameter.…”
Section: Discussionmentioning
confidence: 99%
“…However, a scoring system that is cost effective, repeatable, and can be applied quickly in the preoperative period is quite important in the AA diagnosis algorithm especially for young residents and emergency physicians working in rural areas (9,10).…”
Section: Introductionmentioning
confidence: 99%